Citrate-stabilized gold nanoparticles as negative controls for measurements of neurite outgrowth. Issue 1 (February 2015) - Jeerage, Kavita M.; Oreskovic, Tammy L.; Curtin, Alexandra E.; Sanders, Aric W.; Schwindt, Rani K.; Chiaramonti, Ann N.
Highlights 30 nm gold nanoparticles (AuNPs) are stable in low-serum culture medium for 10 days. Focused ion beam milling exposes AuNPs within cellular cross sections. AuNPs can be individually resolved by helium ion microscopy. 0.5 μg/mL AuNPs do not alter metabolism or neurite outgrowth after 10 days exposure. Cross-slide coefficient of variation for controls (Li+ or AuNPs) is less than 10%.